The Effect of Entrepreneurship Course and Entrepreneurial Skills on the Entrepreneurial Motivation of Economics Students - Cut Darmadani; Choirul Nikmah (Journal of Psychology and Culture Behavior in SDGs, 2025)
Objective: The purpose of this study is to analize how entrepreneurship courses and entrepreneurship skills affect students' and entrepreneurial skills affect students' desire for entrepreneurship at the Faculty of Economics and Business, Surabaya State University. Method: An explanatory quantitative method was used for this study, through questionnaires and analysed using multiple linear regression in SPSS on economics students of the Faculty of Economics and Business, State University of Surabaya.  Results: Students' motivation for entrepreneurship is positively influenced by both entrepreneurship courses and entrepreneurship skills. In addition, entrepreneurship skills turned out to increase student motivation more than entrepreneurship courses.  Novelty: The combination of two significant predictors —namely, the entrepreneurship course and entrepreneurial skill —has not been previously studied in relation to entrepreneurial motivation among economics students. A new contribution found is the importance of updating the entrepreneurship course in line with market developments and focusing on enhancing entrepreneurial skills at the university level.